2018
DOI: 10.1515/hukin-2017-0181
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Isokinetic Shoulder Evaluation and Fitness Characteristics of Elite French Female Water-Polo Players

Abstract: Swimming and throwing are involved in water-polo player performance. These movements have a common biomechanical basis in the use of the internal shoulder rotation and adductor muscles. The aim of the study was to evaluate the relationship between shoulder isokinetic evaluation and throwing velocity as well as swimming performance in female water-polo players. Fifteen high level water-polo players completed two isokinetic shoulder evaluations to determine peak torque of shoulder rotators of the dominant should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
1
7
0
2
Order By: Relevance
“…While studying this, Chelly et al (2014) concluded that after eight weeks of plyometric training, there was an increase in throwing velocity among elite handball players, but they also mention that the application of all training methods should be tested in all populations, determining the real effect that occurs within each group of subjects, especially in women ( Chelly et al, 2014 ). Additionally, it is known that the torque produced during internal and external rotation movements of the shoulder, evaluated through isokinetic instruments, correlates significantly with throwing velocity in water polo players ( Olivier and Daussin, 2018 ), and it must be taken into account. Since isokinetic movements do not resemble the reality of sports, it is necessary to implement evaluations and training that allow sports movements to be controlled in a natural way.…”
Section: Introductionmentioning
confidence: 99%
“…While studying this, Chelly et al (2014) concluded that after eight weeks of plyometric training, there was an increase in throwing velocity among elite handball players, but they also mention that the application of all training methods should be tested in all populations, determining the real effect that occurs within each group of subjects, especially in women ( Chelly et al, 2014 ). Additionally, it is known that the torque produced during internal and external rotation movements of the shoulder, evaluated through isokinetic instruments, correlates significantly with throwing velocity in water polo players ( Olivier and Daussin, 2018 ), and it must be taken into account. Since isokinetic movements do not resemble the reality of sports, it is necessary to implement evaluations and training that allow sports movements to be controlled in a natural way.…”
Section: Introductionmentioning
confidence: 99%
“…Assessing rotator muscle imbalance in swimmers thus appears highly relevant and feasible in clinical settings using isokinetic testing, which is an objective, useful and reliable tool to quantify muscular strength and imbalances Journal of Human Kinetics -volume 75/2020 http://www.johk.pl (Batalha et al, 2013;Collado-Mateo et al, 2018;Olivier and Daussin, 2018). Strength imbalances are evaluated using the conventional ratio, calculated as the ratio between ER and IR peak torques (PTs) in a concentric (conER:conIR) or eccentric contraction mode (eccER:eccIR).…”
Section: Introductionmentioning
confidence: 99%
“…Maximum torque flexion of the shoulder at Post 1, Post 2, Post 3 and Post 4 was higher than that at baseline and the flexor muscle strength increased approximately 33 min after acupuncture. The enhancement of the maximum torque is mainly due to the complementary centripetal/centrifugal contraction of the muscles, which results in increased peak torques when the antagonist and active muscles contract synchronically and improve performance [ 26 ]. Past studies have shown that 10 min electrical nerve stimulation of the muscles around the knee joint of endurance athletes can increase the peak limb torque value after exercise and improve the anti-fatigue ability of endurance athletes [ 19 ].…”
Section: Discussionmentioning
confidence: 99%